HUBUNGAN PERSEPSI SISWA TENTANG MANAJEMEN KURIKULUM DAN KECERDASAN SPIRITUAL SISWA DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK - Khasanah Khasanah; Ispurwanti Ispurwanti (Akademika : Jurnal Teknologi Pendidikan, 2024)
This study aims to determine the positive relationship between students' perceptions of curriculum management on Aqidah Akhlak Learning Outcomes. To find out the positive relationship between students' spiritual intelligence on Aqidah Akhlak Learning Outcomes. To find out the positive relationship between students' perceptions of curriculum management and students' spiritual intelligence together with the Aqidah Akhlak Learning Outcomes at Madrasah Aliyah Bekasi Regency. This type of research is a descriptive correlation research. The population is by taking class XI students from three Madrasah Aliyah, namely 30 students of Class X1 Mas Nur Al Ghozy, 30 students of Class X1 Mas Al Ajhariyah, 30 students of Class X1 Mas Plus Roudhotul Muhibbin Bekasi, the sample in this study was 90 people. The analysis technique used is a quantitative analysis technique using the statistical program SPSS (Statistical Product and Service Solutions) version 20 by processing linearity test data, homogeneity test. and statistical hypothesis. The results of the study show that there is a positive relationship between curriculum management and the learning outcomes of Aqeedah Akhlak students of class XI Madrasah Aliyah, Bekasi Regency. There is a positive relationship between spiritual intelligence and the learning outcomes of Aqidah Akhlak students of class XI Madrasah Aliyah, Bekasi Regency. There is a positive relationship between curriculum management and spiritual intelligence with the learning outcomes of Aqeedah Akhlak students of class XI Madrasah Aliyah, Bekasi Regency..